The use of clil methodology to improve the english vocabulary of students - Merchán Cedillo, Milena Beatriz; Mora Aguilar, Luisa Fabiana (Machala: Universidad Técnica de Machala, 2024)
The present research aims to develop a class system applying the Content and Language Integrated Learning (CLIL) methodology to contribute to the improvement of English vocabulary acquisition in students of 2nd A Baccalaureate at Nueve de Octubre School. The intervention is based on the implementation of a CLIL class system, focusing on expanding and enhancing vocabulary with priority given to factors related to semantics, pronunciation, and writing. The research was conducte d with the participation of 38 students, using a nonexperimental design of Participatory Action Research under the support of a qualitative methodological paradigm. A pedagogical test was carried out to verify the data obtained from an observation applied in previous interactions wi th the student group to assess their prior knowledge related to vocabulary. After identifying issues in the English language learning process of the students, the intervention proposal is defined, and the class system is implemented. The intervention took place in two classes, addressing topics from the Biology subject. Through the results of observations and an interview, a significant improvement in vocabulary production was evident. This study highlights the effectiveness of the CLIL methodology in Engli sh vocabulary learning, suggesting its continuous implementation to enhance language skills contextually.
La presente investigación tiene como objetivo elaborar un sistema de clases aplicando la metodología Content and Language Integrated Learning CLIL para contribuir a la mejora de la adquisición del vocabulario en inglés en estudiantes de 2do Bachillerato paralelo A del Colegio Nueve de Octubre. La intervención se basa en la implementación de un sistema de clases CLIL, enfocada a la expansión y mejoramiento del vocabulario dando prioridad a los factores referentes a la semántica, pronunciación y escritura. La investigación se llevó a cabo con la participación de 38 educandos, utilizando un diseño no experimental de tipo Investigación Acción Participativa bajo la sustentación de un paradigma metodológico cualitativo. Se realizó una prueba pedagógica con el objetivo de corroborar los datos obtenidos de una la observación aplicada en interacciones anteriores con el grupo de estudiantes para evaluar sus conocimientos previos referentes al vocabulario. Después de identificar los problemas en el proceso de aprendizaje del idioma inglés de los estudiantes, se define la propuesta de intervención y se procede a implementar el sistema de clase. La intervención se desarrolló en dos clases, abordando temas de la asignatura de Biología y junto a los resultados de las observaciones y una entrevista, se evidenció una mejora significativa en la producción del vocabulario, Este estudio resalta la eficacia de la metodología CLIL en el aprendizaje del vocabulario en inglés, sugiriendo su implementación continua para mejorar las habilidades lingüísticas de manera contextual.
Keywords: METHODOLOGY; VOCABULARY; PARTICIPATORY; RESEARCH